THE INFLUENCE OF LEADERSHIP AND WORK CULTURE ON THE PERFORMANCE OF ASN TEACHERS THROUGH WORK DISCIPLINE AT STATE HIGH SCHOOL LEVEL IN CAMPALAGIAN SUB-DISTRICT - muh irfan ulpa (Scientia integritas Utama, 2022)
This research uses a quantitative research based on the type of approach that aims to examine and analyze the influence of leadership, work culture, work discipline on the performance of ASN teachers at State Senior High Schools in the Campalagian District. The population in this study amounted to 57 people with saturated sampling, namely the entire population. This study used the Path Analysis and Sobel Test methods to determine the direct and indirect effects of variables. The research consists of independent variables of leadership and work culture, the dependent variable is the performance of ASN teachers, and work discipline as an intervening variable between the independent and dependent variables. The results of this study indicate (1) leadership has a positive and significant effect on the work discipline of ASN teachers, (2) work culture has a positive and significant effect on ASN teacher work discipline, (3) leadership has a positive and significant effect on ASN teacher performance, (4) work culture has a positive and significant effect on ASN teacher performance, (5) work discipline has a positive effect and significant effect on performance, ASN teachers (6) leadership has a positive and significant effect on performance through the work discipline of ASN teachers. and (7) work culture has a positive and significant effect on performance through the work discipline of ASN teachers at State Senior High Schools in the Campalagian District. (5) work discipline has a positive and significant effect on performance, ASN teachers (6) leadership has a positive and significant effect on performance through the work discipline of ASN teachers. and (7) work culture has a positive and significant effect on performance through the work discipline of ASN teachers at State Senior High Schools in the Campalagian District. (5) work discipline has a positive and significant effect on performance, ASN teachers (6) leadership has a positive and significant effect on performance through the work discipline of ASN teachers. and (7) work culture has a positive and significant effect on performance through the work discipline of ASN teachers at State Senior High Schools in the Campalagian District.